Verification of Knoop indenters with a Vickers-addressed optical system. (15th October 2020) - Prato, Andrea; Origlia, Claudio; Germak, Alessandro
Highlights: A model for Knoop indenters verification with Vickers-addressed systems is shown. Comparison of experimental and reference values provided compatible results. The method can be easily implemented without any modification of the apparatus. Abstract: ISO 4545-2 and 4545-3 of Knoop hardness tests require the geometrical verification of the indenters. INRiM hardness laboratory, in cooperation with Galileo-LTF®, has developed the Gal-Indent optical measuring system for the verification of Vickers indenters. This system can measure the vertex angles between two opposite faces, the quadrilateral base angles and the pyramid axis tilt angle. Using these measured quantities as inputs of a suitable geometrical model, the angles between the opposite edges at the vertex of Knoop indenters, nominally 172.5° and 130°, and the angle between the pyramid and indenter holder axes can be verified with an expanded uncertainty of 0.05°. Comparison of experimental measurements performed on three different Knoop indenters, previously verified by an accredited laboratory, shows compatible results. The proposed geometrical model could be easily implemented by laboratories that adopt similar measuring systems addressed for the verification of Vickers indenters without any modification of the experimental apparatus.